2020
DOI: 10.1177/0271678x19898148
|View full text |Cite
|
Sign up to set email alerts
|

DSC perfusion-based collateral imaging and quantitative T2 mapping to assess regional recruitment of leptomeningeal collaterals and microstructural cortical tissue damage in unilateral steno-occlusive vasculopathy

Abstract: Leptomeningeal collateral supply is considered pivotal in steno-occlusive vasculopathy to prevent chronic microstructural ischaemic tissue damage. The aim of this study was to assess the alleged protective role of leptomeningeal collaterals in patients with unilateral high-grade steno-occlusive vasculopathy using quantitative (q)T2 mapping and perfusion-weighted imaging (PWI)-based collateral abundance. High-resolution qT2 was used to estimate microstructural damage of the segmented normal-appearing cortex. Vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 51 publications
3
7
0
Order By: Relevance
“…Our results confirm the previously reported finding that activation of leptomeningeal collaterals 33 , 43 suggests a compromised hemodynamic status. A similar finding was reported by Strother et al.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results confirm the previously reported finding that activation of leptomeningeal collaterals 33 , 43 suggests a compromised hemodynamic status. A similar finding was reported by Strother et al.…”
Section: Discussionsupporting
confidence: 92%
“…Comparably, a recent study using perfusion weighted imaging and quantitative T2* mapping based assessment of leptomeningeal collaterals concluded that increased leptomeningeal collateral supply cannot necessarily be regarded as a sign of effective compensation in patients with high-grade steno-occlusive vasculopathy. 43 Our results confirm this hypothesis. Moreover, with significantly lower BOLD-CVR values in patients with activated leptomeningeal collaterals (independent of ophthalmic activation) as compared to patients with activated ophthalmic collaterals without leptomeningeal collaterals, a clear priority in activation of secondary collaterals is detectable.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The perforating (or deep perforating) arteries, arising from the arterial circle of Willis or from its immediate branches, especially the lenticulostriate artery, exclusively supplied by perforating end arteries originating from the M1 segment of the middle cerebral artery. 28 , 29 It comes out vertically at the bifurcations, once the BP increases suddenly, the impact of blood flow will enhance in the anatomical vertical position, 30 if the BP reaches the points rupture of vessel wall, it may tend to bleeding, such as basal ganglia, the most common site of bleeding. Superficially, although they were terminal vessels stemming from the subarachnoid circulation, the arterioles have branches from the external carotid artery(ECA), and both cortical and subcortical structures are adequately supplied by the posterior cerebral artery, 20 , 31 , 32 forming an anastomotic network on the surface of the hemispheres.…”
Section: Discussionmentioning
confidence: 99%
“…Since these pathological tissue alterations are detectable with qMRI, an application of these techniques in patients with cerebrovascular disease can be expected to be a promising approach. In fact, significant increases of T2 values were observed in normal-appearing WM and normal-appearing cortical GM affected by chronic hypoperfusion in patients with unilateral high-grade carotid-occlusive disease ( 44 , 45 ). The relative prolongation of the T2 relaxation time correlated with the degree of hemodynamic impairment, indicating that T2 mapping detects gliotic tissue conversion, demyelination and enlargement of the extracellular compartment related to local hypoperfusion ( 44 , 45 ).…”
Section: Qmri In Cerebrovascular Diseasementioning
confidence: 99%